THE EXPERIENCES OF USING TIKTOK AS A SOURCE OF PARENTING KNOWLEDGE - Niken Dwi Widyastuti; Ali Formen (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2026)
This paper aims to explore and analyze young mothers' experiences of using TikTok as a source of parenting knowledge. Using a mixed method approach, data was collected through google forms consisting of closed and open-ended questions. A total of 92 respondent mothers with young children participated in this study. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using a thematic analysis approach and presented in a descriptive narrative. The results showed that most respondents found parenting content on TikTok helpful, and accessed it at flexible times to suit their daily routines. TikTok is considered superior to other social media because it presents information in a concise, practical and easy-to-understand style. Despite the high level of trust in influencers, the majority of mothers still verify information through other sources, reflecting active digital literacy. Some respondents stated that there has been a significant change in parenting. These results suggest that TikTok is not just an entertainment platform, but also serves as a relevant and adaptive informal learning space for young mothers. This research provides a snapshot of the shifting ways parents access and internalize parenting information in the digital age.